Public interest in the digital transformation accelerated by the COVID-19 pandemic and perception of its future impact - Joo-Young Park; Kangsun Lee; Doo Ryeon Chung (The Korean Journal of Internal Medicine, 2022)
Background/Aims The coronavirus disease 2019 (COVID-19) pandemic has accelerated digital transformation (DT). We investigated the trend of the public interest in technologies regarding the DT and Koreans’ experiences and their perceptions of the future impact of these technologies. Methods Using Google Trends, the relative search volume (RSV) for topics including “coronavirus,” “artificial intelligence,” “cloud,” “big data,” and “metaverse” were retrieved for the period from January 2020 to January 2022. A survey was conducted to assess the population’s knowledge, experience, and perceptions regarding the DT. Results The RSV for “metaverse” showed an increasing trend, in contrast to those for “cloud,” “big data,” and “coronavirus.” The RSVs for DT-related keywords had a negative correlation with the number of new weekly COVID-19 cases. In our survey, 78.1% responded that the positive impact of the DT on future lives would outweigh the negative impact. The predictors for this positive perception included experiences with the metaverse (4.0-fold) and virtual reality (VR)/augmented reality (AR) education (3.8-fold). Respondents predicted that the biggest change would occur in the healthcare sector after transportation/communication. Conclusions Koreans’ search interest for “metaverse” showed an increasing trend during the COVID-19 pandemic. Koreans believe that DT will bring about big changes in the healthcare sector. Most of the survey respondents have a positive outlook about the impact of DT on future life, and the predictors for this positive perception include the experiences with the metaverse or VR/AR education. Healthcare professionals need to accelerate the adoption of DT in clinical practice, education and training.